A Novel Mutation in the Mitochondrial DNA Cytochrome b Gene (MTCYB) in a Patient with Prader Willi Syndrome. (March 2015) - Yiş, Uluç; Ezgü, Fatih Süheyl; Karakaya, Pakize; Polat, İpek; Arslan, Nur; Çankaya, Tufan; Bozkaya, Özlem Giray; Kurul, Semra Hız
In recent years, it has been suggested that defects in energy metabolism may accompany Prader Willi syndrome. Mutations in the mitochondrial cytochrome b gene have been commonly associated isolated mitochondrial myopathy and exercise intolerance, rarely with multisystem disorders. The authors describe a novel mutation (mt. 15209T>C) in mitochondrial cytochrome b gene in a 2-year-old girl with Prader-Willi syndrome with a clinical history of lactic acidosis attacks, renal sodium loss, hepatopathy, progressive cerebral atrophy, and sudden death. The authors suggest that atypical clinical findings in patients with Prader-Willi syndrome should direct the physician to search for a mitochondrial disease.